SOME ASPECTS OF SUSTAINABILITY AND SYNERGY IN THE EMERGING TEACHER TRAINING - Ratniece, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The emerging English as a foreign language teachers develop their professional competence better if they participate in global informal studies by collaboration involving global synergy issues, which develop higher their professional competence. Analysis of theoretical sources and empirical research. Results of global informal studies organized by 12 higher education teacher training institutions analyzed. Global learning shared in master classes, lectures, case studies in Austrian schools, text books for learning English compared. Lessons conducted by international teams on global learning analyzed. Results disclosing the reactions of the participants included. Valid knowledge on teaching English and sustainability gained. Synergy brings valuable knowledge needed for professional competence development on teaching/learning.